Genome-wide Analysis of Transcript Abundance and Translation in Arabidopsis Seedlings Subjected to Oxygen Deprivation - BRANCO-PRICE, CRISTINA (Ann Bot, 2005)
• Background and Aims DNA microarrays allow comprehensive estimation of total cellular mRNA levels but are also amenable to studies of other mRNA populations, such as mRNAs in translation complexes (polysomes). The aim of this study was to evaluate the role of translational regulation in response to oxygen deprivation (hypoxia). • Methods Alterations in total cellular and large polysome (≥ five ribosomes per mRNA) mRNA levels were monitored in response to 12 h of hypoxia stress in seedlings of Arabidopsis thaliana with a full-genome oligonucleotide microarray. • Key Results Comparison of two mRNA populations revealed considerable modulation of mRNA accumulation and diversity in translation in response to hypoxia. Consistent with the global decrease in protein synthesis, hypoxia reduced the average proportion of individual mRNA species in large polysome complexes from 56·1 % to 32·1 %. A significant decrease in the association with translational complexes was observed for 77 % of the mRNAs, including a subset of known hypoxia-induced gene transcripts. The examination of mRNA levels of nine genes in polysomes fractionated through sucrose density gradients corroborated the microarray data. Gene cluster analysis was used to identify mRNAs that displayed co-ordinated regulation. Fewer than half of the highly induced mRNAs circumvented the global depression of translation. Moreover, a large number of mRNAs displayed a significant decrease in polysome association without a concomitant decrease in steady-state accumulation. The abundant mRNAs that encode the ribosomal proteins behaved in this manner. By contrast, a small group of abiotic and biotic stress-induced mRNAs showed a significant increase in polysome association, without a change in abundance. Evaluation of quantitative features of mRNA sequences demonstrated that a low GC nucleotide content of the 5′-untranslated region provides a selective advantage for translation under hypoxia. • Conclusions Alterations in transcript abundance and translation contribute to the differential regulation of gene expression in response to oxygen deprivation.